Enhancing the role of nurses in breastfeeding preterm infants† - Yang Yuan-Yuan; Chen Jia-Yue; Liu Hui-Juan (Sciendo, 2023)
The provision of breast milk and breastfeeding is recommended for preterm infants. Multidisciplinary cooperation is required to promote breastfeeding. Nurses play important roles in breastfeeding preterm infants. First, nurses are strong advocates to help families be aware of the significance of breastfeeding. Second, nurses are educators providing technical and emotional support to pregnant and lying-in women. Third, nurses are coordinators in a multidisciplinary team. Nurses' unawareness of the importance of breastfeeding, knowledge deficit, and unsupportive lactation policy are barriers to breastfeeding promotion for preterm infants. It is therefore suggested that hospital administrators provide appropriate breastfeeding policies, set up posts, and ensure nurses' responsibilities in breastfeeding. Additionally, tailored training should be strengthened to improve nurses' knowledge and skills and thereby enable them to fully exert their roles in the breastfeeding promotion of preterm infants.